2015
DOI: 10.1063/1.4905311
|View full text |Cite
|
Sign up to set email alerts
|

Defect study of Cu2ZnSn(SxSe1−x)4 thin film absorbers using photoluminescence and modulated surface photovoltage spectroscopy

Abstract: Defect states in Cu2ZnSn(SxSe1−x)4 thin films with x = 0.28, 0.36, and 1 were studied by combining photoluminescence (PL) and modulated surface photovoltage (SPV) spectroscopy. A single broad band emission in the PL spectra was observed and can be related to quasi-donor-acceptor pair transitions. The analysis of the temperature dependent quenching of the PL band (x = 0.28, 0.36, and 1) and SPV (x = 0.28) signals resulted in activation energies below 150 meV for PL and about 90 and 300 meV for SPV. Possible int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Both samples show a red shift of the band maximum up to ≈150 K and blue shift at higher temperatures. Similar dependencies were observed previously for CZTSSe solid solutions with quasi donor‐acceptor pair (QDAP) emission and detailed explanations can be found elsewhere . It is notable that the PL peak of the AT treated sample exhibits blue shift (around 10 mV) in the whole range of temperatures with respect to the reference one.…”
Section: Resultssupporting
confidence: 84%
“…Both samples show a red shift of the band maximum up to ≈150 K and blue shift at higher temperatures. Similar dependencies were observed previously for CZTSSe solid solutions with quasi donor‐acceptor pair (QDAP) emission and detailed explanations can be found elsewhere . It is notable that the PL peak of the AT treated sample exhibits blue shift (around 10 mV) in the whole range of temperatures with respect to the reference one.…”
Section: Resultssupporting
confidence: 84%
“…These fluctuations usually determine the asymmetric shape of PL bands, where the shape of the low energy side of the PL spectra is determined by the density of states function. In kesterite samples, γ values in the range γ≈25-80 meV were found [2,3,5,29,[31][32][33][34][35]. Typical low-temperature measurements for kesterites show a broad peak with increasing width and assymmetry for higher sulfur concentrations as shown in figure 2(a).…”
Section: Intrinsic Defects In Kesteritesmentioning
confidence: 90%
“…PL and admittance spectroscopy (AS) are the most used experimental methods to study defects in kesterites. PL studies have shown that most of the kesterite materials show properties that are typical for highly doped and compensated semiconductors [2,5,[27][28][29]. In kesterites, the high doping originates from the very high concentration of charged intrinsic defects (>10 20 cm −1 ) that cause widening of the defect levels within the forbidden gap and induce the spatial potential fluctuations and formation of band tails.…”
Section: Intrinsic Defects In Kesteritesmentioning
confidence: 99%
“…A summary of some of these recombination models can be found in the review of Teixeira et al [7]. The luminescence observed in CZTSSe is energetically far below the band gap and is often attributed to donor-acceptor pair transitions involving electro static potential fluctuations (so called quasi donor-acceptor pair transitions) [8]. The fluctuations lead to band tails [9] thus influencing the PL behavior.…”
Section: Introductionmentioning
confidence: 98%